New Method of Cryptography With Python Code Using Elzaki Transform and Linear Combination of Function - Raut, P. P.; Hiwarekar, A. P. (Communications in Mathematics and Applications, 2023)
In today’s digital world, cybercrime has become biggest challenge to face in order to keep the confidential information secure from intruders. The security mechanisms used to curb the cyber-attacks, need to be improvised on constant basis with the help of advanced mathematical techniques. This paper deals with new cryptography based iterative method by using successive Elzaki transform of linear combination of functions for encryption and corresponding inverse Elzaki transform for decryption. Starting with a detailed procedure, we presented our work in the form of result. Further, it is generalized and then we applied the iterative method for making our algorithm more secure. We also implemented this method programmatically using PYTHON language which fits current needs. Finally, we illustrate our results with suitable examples.